Plan de marketing para la empresa D`Ensueños de la ciudad de Loja - Parra Feijoo, Emilio José (2015)
This research was conducted at the company D'ENSUEÑOS city of Loja, it has had to identify and implement new strategies to stay on the market, but these efforts have not been enough because internally in the company there are some shortcomings that must be improved as a Marketing Plan. With this background we have seen the need for a marketing plan to identify and implement future strategies to have better chances of success through consistent positioning the company in the market Lojano. For this specific objectives were developed in the thesis project including, primarily a Diagnosis of the company that allowed us to consider relevant aspects of the company that exist at the present time is made. With respect to methods and techniques used for conducting this research, literature survey, document review, direct observation of the operation and services provided by the company were applied; plus an interview to the Manager was made; surveys were administered to 396 permanent customers of the company contained in the database of the same and a total of 5 surveys of employees working in the company to know the positioning of the company in the market and through her information in order to have a clearer vision and reliable solutions that were required to raise was collected. From this information it was determined result in Matrix EFI 2.48, a result which shows that the weaknesses of the company are more salient than strengths. Also in the External Analysis a score of 2.44 was obtained; which means that the threats on the market have a marked predominance over existing market opportunities. To make the interpretation and discussion of results obtained in the surveys, analytical and descriptive method was used. Strengths, weaknesses, opportunities and threats to the company: a SWOT analysis, which identified the was also performed. With the development of these elements strategies for improving internal and external aspects were built, enhancing their strengths, to seize opportunities, reduce weaknesses and neutralize threats; the determination of these internal and external factors which allowed making high-impact matrix and weighting to structure a new SWOT matrix; Also deductive and inductive method was used to detect the current reality of self in relation to the functions and activities performed by employees as well as the processing of the collected information. Finally a proposal based on a Marketing Plan was undertaken to improve the operation and services of the company; is the same as the implementation of four targets. The whole scheme is proposed to be conducted with a total investment of $ 21.020,00. Finally, conclusions and recommendations presented have been determined, then the study conducted by the marketing planning process, the same that will be brought to the attention of executives at the company for later execution